Vertical miscentering and effect on radiation dose to the lens in computed tomography head examination: A systematic review - Kamal, Izdihar; Mohd Yusof, Mohd Khairul Fazwan; Abdul Karim, Muhammad Khalis; Che Mut, Nur Anis Izzati; Mohamad Tajudin, Suffian; Abdul Jamil, Aminatul Saadiah (Elsevier, 2025)
Computed tomography (CT) scanners are the foremost instruments for detecting pathology in the human body. The rising used of CT scanner to assess pathological and injuries to the area of brain has prompted concerns about the radiation dose absorbed by radiosensitive organs, particularly the eye lens. The purpose of this systematic review was to investigate the impact of vertical miscentering on the radiation dose to the lens during plain head CT examination. A systematic evaluation of the existing literature was performed utilizing the MyEBSCO platform, which encompasses 11 electronic databases, including MEDLINE and CINAHL. The research conducted from 2014 to 2025 was examined to ascertain the correlation among vertical miscentering, absorbed lens dose, and image quality. The exhaustive search found 59 relevant publications, all of which were rigorously reviewed. Of these, 9 papers advanced to full-text screening, and 5 were eventually included in the review. The findings consistently demonstrate that vertical miscentering significantly increases the absorbed dose to the lens. However, image quality remains largely unaffected when the miscentering is less than 5 cm inferiorly and image noise appears minimally impacted by minor miscentering. All reviewed studies reported an inverse-proportional relationship between vertical miscentering and lens dose. The literature collectively underscores that precise patient centering is critical for minimizing radiation exposure to the lens without compromising diagnostic image quality. Ensuring accurate positioning of the patient's head at the gantry isocenter remains essential.